2018
DOI: 10.1016/j.antiviral.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Broad-spectrum antiviral activity of the eIF4A inhibitor silvestrol against corona- and picornaviruses

Abstract: Coronaviruses (CoV) and picornaviruses are plus-strand RNA viruses that use 5' cap-dependent and cap-independent strategies, respectively, for viral mRNA translation initiation. Here, we analyzed the effects of the plant compound silvestrol, a specific inhibitor of the DEAD-box RNA helicase eIF4A, on viral translation using a dual luciferase assay and virus-infected primary cells. Silvestrol was recently shown to have potent antiviral activity in Ebola virus-infected human macrophages. We found that silvestrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
183
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(197 citation statements)
references
References 25 publications
2
183
0
1
Order By: Relevance
“…Viral mRNAs also contain structured 5′-UTRs (Madhugiri et al, 2015;Schlereth et al, 2016), suggesting that viral protein synthesis may also be eIF4A-dependent. Indeed, we have shown that the specific eIF4A inhibitor Silvestrol, a plant-derived rocaglate, has broad-spectrum antiviral activity at non-cytotoxic concentrations in a low nanomolar range (Müller et al, 2018a). Silvestrol inhibits the replication of RNA viruses representing different virus families, such as Ebola-(EBOV), corona-(CoV), Zika-(ZIKV), Chikungunya-(CHIKV) and hepatitis E (HEV) viruses (Müller et al, 2018a;Biedenkopf et al, 2017;Elgner et al, 2018;Glitscher et al, 2018;Henss et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral mRNAs also contain structured 5′-UTRs (Madhugiri et al, 2015;Schlereth et al, 2016), suggesting that viral protein synthesis may also be eIF4A-dependent. Indeed, we have shown that the specific eIF4A inhibitor Silvestrol, a plant-derived rocaglate, has broad-spectrum antiviral activity at non-cytotoxic concentrations in a low nanomolar range (Müller et al, 2018a). Silvestrol inhibits the replication of RNA viruses representing different virus families, such as Ebola-(EBOV), corona-(CoV), Zika-(ZIKV), Chikungunya-(CHIKV) and hepatitis E (HEV) viruses (Müller et al, 2018a;Biedenkopf et al, 2017;Elgner et al, 2018;Glitscher et al, 2018;Henss et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have shown that the specific eIF4A inhibitor Silvestrol, a plant-derived rocaglate, has broad-spectrum antiviral activity at non-cytotoxic concentrations in a low nanomolar range (Müller et al, 2018a). Silvestrol inhibits the replication of RNA viruses representing different virus families, such as Ebola-(EBOV), corona-(CoV), Zika-(ZIKV), Chikungunya-(CHIKV) and hepatitis E (HEV) viruses (Müller et al, 2018a;Biedenkopf et al, 2017;Elgner et al, 2018;Glitscher et al, 2018;Henss et al, 2018). Notably, Silvestrol showed good bioavailability (Sarahdi et al, 2011), in vivo antiviral activity (Todt et al, 2018) and remarkably low https://doi.org/10.…”
Section: Introductionmentioning
confidence: 99%
“…This blocks helicase activity and inhibits protein translation. A recent in vitro study demonstrated that silvestrol has anti-MERS-CoV activity [73]. No clinical data or studies support its use in vivo at the present time.…”
Section: Silvestrolmentioning
confidence: 84%
“…Inhibition of viral propagation by treatment with silvestrol occurred more rapidly than any effects on cellular functions and an IC 50 lower than 1 nM was observed (Biedenkopf et al, 2017). Very recently, potent antiviral activities were also reported for coronaviruses including MERS-CoV and picornaviruses revealing broad-spectrum activities (Muller et al, 2018). For HEV, we observed also an antiviral activity at low nanomolar concentrations for the human gts 1 and 3, a gt3 swine isolate as well as for a viral variant, which was identified in HEV-infected patients and confers enhanced replication fitness (Fig.…”
Section: Discussionmentioning
confidence: 96%